1998
DOI: 10.1097/00006982-199805000-00030
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Products Increase Retinal Vascular Endothelial Growth Factor Expression.

Abstract: Advanced glycation end products (AGEs) are linked with the development of diabetic retinopathy; however, the pathogenic mechanisms are poorly defined. Vascular endothelial growth factor (VEGF) levels are increased in ischemic and nonischemic diabetic retina, and VEGF is required for the development of retinal and iris neovascularization. Moreover, VEGF alone can induce much of the concomitant pathology of diabetic retinopathy. In this study, we found that AGEs increased VEGF mRNA levels in the ganglion, inner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
122
0
4

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(130 citation statements)
references
References 0 publications
4
122
0
4
Order By: Relevance
“…These include not only glucose [37] but also advanced glycation end products (AGEs) [38] and protein kinase-C activation [39,40]. Of particular relevance to our study, angiotensin II also stimulates VEGF expression, an action mediated by the AT1 receptor as indicated by the attenuation of this effect by the AT1 receptor antagonist, losartan [13,41].…”
Section: Discussionmentioning
confidence: 85%
“…These include not only glucose [37] but also advanced glycation end products (AGEs) [38] and protein kinase-C activation [39,40]. Of particular relevance to our study, angiotensin II also stimulates VEGF expression, an action mediated by the AT1 receptor as indicated by the attenuation of this effect by the AT1 receptor antagonist, losartan [13,41].…”
Section: Discussionmentioning
confidence: 85%
“…In addition, glucose degradation products and advanced glycation end products are known to induce VEGF expression in vitro, although the in vivo relevance of these pathways remains to be demonstrated. Laser burns destroy the ischemic retinal tissue that is a source of intraocular VEGF (25,26), which is followed by alterations in gene expression, as has been observed in mice retina after PRP. Specifically, genes inhibiting VEGF expression (e.g., angiotensin II type 2 receptor) were found to be upregulated, whereas genes promoting VEGF expression (e.g., fibroblast growth factors 14 and 16, interleukin-1␤, calcitonin receptor-like receptor, and plasminogen activator inhibitor 2) were found to be downregulated (27).…”
Section: Research Design Andmentioning
confidence: 83%
“…The breakdown of the BRB occurs in patients with diabetic retinopathy [27]. Several studies have suggested that AGEs induce vasopermeability of the retina by increasing VEGF production [14,23,[28][29][30][31] and disrupt the BRB by decreasing tight junction proteins, such as occludin and ZO-1 [32]. However, the role of AGEs in diabetic neuropathy remains unclear.…”
Section: Discussionmentioning
confidence: 99%